2017
DOI: 10.2741/e803
|View full text |Cite
|
Sign up to set email alerts
|

Fungal immunomodulatory proteins in the context of biomedicine

Abstract: Fungi represent a large group of biodiverse microorganisms with potential applications ranging from industrial fields to the treatment for human diseases. A large number of pharmacologically active compounds including terpenoids, polysaccharides and proteins have been derived from these microorganisms. Fungal Immunomodulatory Proteins (FIPs) are a group of active compounds that are being considered for the treatment of asthma, allergy, autoimmune diseases and cancer. Here, we discuss the discovery, heterologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 98 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have shown that FIP possess broad spectrum immunomodulatory and anticancer activities, suggesting that they may be promising candidates in clinical disease therapies or for treatment as adjuvant agents 4,17 . FIP can be orally consumed and have high stability when exposed to denaturing conditions 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that FIP possess broad spectrum immunomodulatory and anticancer activities, suggesting that they may be promising candidates in clinical disease therapies or for treatment as adjuvant agents 4,17 . FIP can be orally consumed and have high stability when exposed to denaturing conditions 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments showed that FIP is a potent T cell activator that enhances the immune response by modulating the production of important cytokines and molecular factors (IL-2, IFN-γ, IL-1β, TNF-α etc.) in several vertebrate model systems 4 . The ability of these cytokines to produce a tumour suppressing environment indirectly proves that FIP regulates the immune system and has a cytotoxic effect on tumour cells 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Fungal immunomodulatory proteins (FIPs) are a new class of bioactive proteins reported in fungi, including those popular edible and medicinal mushrooms on the market, such as G. lucidum (LZ-8 or FIP-glu) [ 10 ], F. velutipes (FIP-fve) [ 11 ], V. volvacea (FIP-vvo) [ 12 ], and G. sinensis (FIP-gsi) [ 13 ]. The bioactive effects of FIPs have attracted research interest since their discovery, such as hemagglutination, anti-allergy, anti-inflammation, immunomodulation, and anti-tumor [ 14 , 15 ]. The immune modulators originating from mushrooms stimulate both the innate immune system and the acquired immune system [ 2 ].…”
Section: Introductionmentioning
confidence: 99%